2019
DOI: 10.3233/wor-192960
|View full text |Cite
|
Sign up to set email alerts
|

A job task analysis to describe the physical demands of specialist paramedic roles in the National Ambulance Resilience Unit (NARU)

Abstract: BACKGROUND:The National Ambulance Resilience Unit (NARU) works on behalf of each National Health Service (NHS) Ambulance Trust in England to strengthen national resilience and improve patient outcome in challenging pre-hospital scenarios. OBJECTIVE: To conduct a Job Task Analysis and describe the physical demands of NARU roles. METHODS: A focus group was conducted to describe the physically demanding tasks performed by NARU personnel. Subsequently, the physical demands of the identified tasks were measured in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Although literature exists on the development of a PES for firefighters and paramedics, there is currently no PES that has been conducted taking into consideration the physical demands associated with the BEMC program (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Although literature exists on the development of a PES for firefighters and paramedics, there is currently no PES that has been conducted taking into consideration the physical demands associated with the BEMC program (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…Implementing an organisation-wide, routine physical capability testing process can be onerous for employers and often involves both theoretical and practical challenges to overcome to ensure PES are properly administered. Some of the more theoretical considerations may often come in the development stage of establishing a PES, including defining role related tasks [44,45], determining minimum performance standard(s) [1,12] or determining appropriate cut-scores for PES [24,36]. The practical issues may well often follow and be dominated by factors such as the resources and logistics needed to implement a service-wide testing programme for hundreds, or even thousands of employees spread across multiple work sites.…”
Section: Discussionmentioning
confidence: 99%
“…Elements of these roles elicit high physical demand, particularly patient handling, stretcher manipulation and loading/unloading necessary equipment (Fischer et al 2017). In the United Kingdom (UK), emergency situations that warrant more specialist capabilities are attended to by the National Ambulance Resilience Unit (NARU; Rue et al 2019). The NARU works on behalf of each Ambulance Trust within the UK National Health Service and, by deploying specially trained paramedics, strengthens national resilience to a variety of challenging and hazardous emergency scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…The NARU works on behalf of each Ambulance Trust within the UK National Health Service and, by deploying specially trained paramedics, strengthens national resilience to a variety of challenging and hazardous emergency scenarios. As preparatory work for the present study, a task analysis of NARU personnel identified a wide range of highly physically demanding essential tasks spread across three roles: Hazardous Area Response Team (HART); Chemical, Biological, Radiological and Nuclear (CBRN); and Marauding Terrorist Attack (MTA; Rue et al 2019). These roles extend to treatment and/or extraction of casualties at height, in remote, urban and subterranean locations inaccessible by vehicle and from inland water, as well as performing mass decontamination and operating under a variety of terrorist threats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation